Eyelid myokymia caused by a trigeminal schwannoma as determined by the trigeminal‐evoked blink reflex - Eiji Ito; Ryotaro Sugita; Ryuta Saito (Clinical Case Reports)
Abstract A 57‐year‐old man had trigeminal schwannoma in Meckel's cave with eyelid myokymia only. The evaluation of the trigeminal‐evoked blink reflex was useful for confirming eyelid myokymia and contributed to surgical decision‐making. In patients with persistent eyelid myokymia, neurophysiological and imaging evaluations may be useful for determining the underlying pathophysiology.